2018
DOI: 10.33549/physiolres.933779
|View full text |Cite
|
Sign up to set email alerts
|

Akt/eNOS and MAPK Signaling Pathways Mediated the Phenotypic Switching of Thoracic Aorta Vascular Smooth Muscle Cells in Aging/Hypertensive Rats

Abstract: Considerable evidence demonstrates that phenotypic switching of vascular smooth muscle cells (VSMCs) is influenced by aging and hypertension. During phenotypic switching, VSMCs undergo a switch to a proliferative and migratory phenotype, with this switch being a common pathology in cardiovascular diseases. The aim of this study was to explore the joint influence of age and hypertension on thoracic aortic smooth muscle phenotypic switching and the balance of Akt and mitogen-activated protein kinase (MAPK) signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Angiotensin II activates its receptor on the endothelial cell surface triggering formation of reactive oxygen species and activation of several intracellular pathways like MAPK (ERK1/2) and others (Akt, NF-kB, MMPs) (87). A large number of transcription factors are then activated or repressed leading to fibroblast-to-myofibroblast activation, myocyte growth, vascular smooth muscle cell phenotype switching, inflammation, and fibrosis (88,89). In addition to neurohumoral activation, high blood pressure causes direct mechanical stress which can activate the MAPK pathway via various cell-surface proteins (85).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II activates its receptor on the endothelial cell surface triggering formation of reactive oxygen species and activation of several intracellular pathways like MAPK (ERK1/2) and others (Akt, NF-kB, MMPs) (87). A large number of transcription factors are then activated or repressed leading to fibroblast-to-myofibroblast activation, myocyte growth, vascular smooth muscle cell phenotype switching, inflammation, and fibrosis (88,89). In addition to neurohumoral activation, high blood pressure causes direct mechanical stress which can activate the MAPK pathway via various cell-surface proteins (85).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OPN is regulated by the SASP regulator C/EBPβ [69], and Lee et al [70] suggested that hydroxynonenal (HNE) induced OPN expression in HVSMCs via signaling pathways involving AP-1 and C/EBPβ, increasing HVSMCs proliferation and vascular remodeling. Another study demonstrated that hypertension and senescence had a compounding effect on the vascular system and induced OPN expression via the PI3K/ AKT/eNOS and Ras/Raf/MAPK signaling pathways [71].…”
Section: Osteopontinmentioning
confidence: 99%
“…According to experimental data, extracellular signal-regulated (ERK) and p38 MAPK are involved in VSMC phenotype switching, but Jun N-terminal kinase (JNK) is a different story [28,29]. In our previous study, cross-talk occurred between the Akt and MAPK pathways during phenotype switching in aging and hypertensive rats [30].…”
Section: Introductionmentioning
confidence: 99%